A case study of challenges we have in pore pressure prediction techniques for a carbonate reservoir - Rashidi, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Pore pressure prediction has always been a major challenge in the industry. Various attempts to predict pore pressure have been made by researchers to best describe the trend for a given region. Several methods have been published and claimed to work for many fields. This paper provides a case study for an oil field in Iran in order to check the applicability of some of the methods in this field. Eaton's, Holbrook's and Weakley's method are tried and it is found that Eaton's method provides a closer result, if not an accurate one. The details of the formation are stated to study the nature of these methods in such environment. The compaction exponent of Eaton's method is varied to see the variation in the trend for the field. The compaction exponent of 3.0 is found to work fairly well for depths up to 2600m while exponent value of 0.7 works for depth greater than 2600m. It is inferred that not all methods are applicable globally and there exists a need for further research to develop or modify these methods either qualitatively or quantitatively. Â© 2015 IEEE.